(untitled) (Boletín de Investigaciones Marinas y Costeras, 2016)
Callistochiton portobelensis Ferreira 1976 and Ischnochiton kaasi Ferreira, 1987 are reported for the fist time from the Colombian Caribbean. Both species were found in shallow water, under rocks, at Santa Marta in October 2009.